ECB: Quo Vadis? - Sylvester C. W. Eijffinger; Lex H. Hoogduin (Intereconomics, 2018)
The European Central Bank has implemented a very ambitious monetary policy since the financial crisis of 2008, intervening heavily in the eurozone economies. This policy has generated substantial risks to both the ECB's primary task and its independence. It is therefore time for a fundamental evaluation of the ECB's monetary policy strategy.
Keywords: 330